In vitro study of effects of aging and processing conditions on colour change in maxillofacial silicone elastomers - Ebru Demet Cifter; Meltem Ozdemir-Karatas; Adem Cinarli; Erkan Sancakli; Ali Balik; Gulumser Evlioglu (BMC, 2019)
Abstract Background The inherent colour change in maxillofacial silicone elastomers becomes perceptible 6-12 months after fabrication. Determining the factors that accelerate the degradation of the prosthesis can help the clinicians increase its life span. Therefore, the aim of the study was to investigate the effect of time passage, processing temperature, and molding-stone colour on the colour change of maxillofacial silicone elastomers after darkroom storage for 6000 h. Methods A total of ten study molds, each incorporating ten specimen gaps were fabricated using five different colors of dental stones. The gaps were filled with coloured Cosmesil M511 maxillofacial silicone elastomer. Five of the study molds, one of each stone color, were processed at room temperature (25 °C) for 24 h while the remainder were vulcanized at 100 °C for 1 h. Two stainless-steel molds were also fabricated to obtain a total of twenty control-group specimens of the same dimensions that were processed under the same conditions as the study molds. Colour measurements of the vulcanized silicone samples were performed using a Konica Minolta spectrophotometer. Initial measurements were obtained after the blocks were removed from the molds and the final measurements were recorded 6000 h after storage in the dark at 25 °C and 40% relative humidity. The CIEDE2000 colour-difference formula was used to measure the changes in the colour. One-way and two-way ANOVA, and an independent-sample t-test were used for statistical assessments. Results For every group, the colour change exceeded the perceptible thresholds. Thus, either the vulcanization temperature or the colour of the molding stone has a significant effect on the colour change over time. Those samples vulcanized in green and white molding stones at 100 °C exhibited a significantly higher ∆L*, ∆a*, and ∆b* values relative to the samples vulcanized at room temperature. Conclusion The molding-stone colour and vulcanization temperature both affect the degree of colour change after storage in a dark environment. The L*, a*, and b* values for the maxillofacial silicone elastomers are influenced by the direction of the increase or decrease according to the selected colour. This effect varies as the temperature increases.